2010
DOI: 10.1097/01.aoa.0000367022.18535.fc
|View full text |Cite
|
Sign up to set email alerts
|

Using Emergency Obstetric Drills in Maternity Units as a Performance Improvement Tool

Abstract: Background: Obstetric drills are being used increasingly to test, improve, and maintain knowledge and skills related to obstetric emergencies as a means to improve proficiency and efficiency of practitioners. The purpose of this study was to assess the feasibility and usefulness of conducting drills to evaluate the response to obstetric emergencies using a holistic approach that tested the hospital system. Methods: A prospective trial was conducted at three hospitals (two tertiary referral centers and one smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Obstetric drills are increasingly used as a means to test provider skills, improve and maintain provider knowledge, and ensure competency and efficiency of staff, particularly in health facilities where life-threatening emergencies are rarely seen and skills may deteriorate [ 75 ]. In the UK, a survey of obstetric emergency drills showed that half of the centres surveyed already conducted drills, and an additional 14% had a drill programme under development [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obstetric drills are increasingly used as a means to test provider skills, improve and maintain provider knowledge, and ensure competency and efficiency of staff, particularly in health facilities where life-threatening emergencies are rarely seen and skills may deteriorate [ 75 ]. In the UK, a survey of obstetric emergency drills showed that half of the centres surveyed already conducted drills, and an additional 14% had a drill programme under development [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drills are ‘ in situ simulations’ of obstetric emergencies performed in a realistic scenario, often during work and using actors instead of mannequins (23). A qualitative study from Lebanon suggested that antepartum hemorrhage and eclampsia drills improved staff response when the same drills were repeated some months later (24). Other EmOC courses similar to ALSO, for example the RCOG's Life Saving Skills in Obstetrics (25), use mannequins to cover a number of obstetric and neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the audit cycle being completed in order to affect change in birth outcomes was emphasised. 16 Training in reading and interpreting cardiotocographs was also done and emphasis was placed on using correct terminology. 14 This is something which can be easily practised in any centre, at little extra cost, provided the team is open to constructive criticism and striving towards improvement.…”
Section: Main Findingsmentioning
confidence: 99%
“…Similar models have been used as performance improvement tools. 16 Training in reading and interpreting cardiotocographs was also done and emphasis was placed on using correct terminology. This enabled faster recognition of abnormal traces, better communication, and accurate documentation.…”
Section: Main Findingsmentioning
confidence: 99%